2015
DOI: 10.1080/17449057.2015.1051326
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Reserved Seat Design on the Quality of Minority Representation

Abstract: This paper analyzes the effects of electoral rules for reserved seats in parliaments on representatives' ability and motivation to represent minorities. While most previous studies treat reserved seats as a uniform mechanism, the author argues that we can distinguish varieties along two attributes: electorate and candidacy. Limiting electorate means that only minority members can vote for reserved seat candidates, which motivates representatives to defend minority interests with the objective of optimizing re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Following Mala Htun (2004), one of the foundational logics of this work is that institutional mechanisms for representing gender and ethnicity rightly differ: gender is framed as an identity that cuts across partisan divides, and so quotas for female candidates are typically seen as the means to facilitate the election of women, whereas ethnicity is framed as coinciding with political cleavages, and thus reserved seats in legislatures for ethnic groups and parties are seen as the means most likely to facilitate their inclusion in politics. To the extent that Indigeneity is considered in this body of work, the tendency is to explore the inclusion of Indigenous peoples in Western models of political representation, equating them with other ethnic groups and viewing them as similar to migrants, racialized groups or national minorities (Htun, 2004; Krook and O'Brien, 2010; Lublin and Wright, 2013; Bird, 2014; Kroeber, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Following Mala Htun (2004), one of the foundational logics of this work is that institutional mechanisms for representing gender and ethnicity rightly differ: gender is framed as an identity that cuts across partisan divides, and so quotas for female candidates are typically seen as the means to facilitate the election of women, whereas ethnicity is framed as coinciding with political cleavages, and thus reserved seats in legislatures for ethnic groups and parties are seen as the means most likely to facilitate their inclusion in politics. To the extent that Indigeneity is considered in this body of work, the tendency is to explore the inclusion of Indigenous peoples in Western models of political representation, equating them with other ethnic groups and viewing them as similar to migrants, racialized groups or national minorities (Htun, 2004; Krook and O'Brien, 2010; Lublin and Wright, 2013; Bird, 2014; Kroeber, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Lublin and Wright (2013) analysed that reserved seats and lower thresholds increase in minority representation but could not find correlation between reserved seats and substantive representation. With his significant contribution in the literature of politician representation, Kroeber (2017) indicated a positive relationship between the reserved seats representative and substantive representation. Kroeber concluded that political reservation is the only tool for ethnic minorities, which limits the electorate to minority voters only so that representatives could be perfectly accountable to the target group.…”
Section: The Context Of the Studymentioning
confidence: 99%
“…Kroeber concluded that political reservation is the only tool for ethnic minorities, which limits the electorate to minority voters only so that representatives could be perfectly accountable to the target group. Under this condition, minority representatives can achieve the terms of substantive representation (Kroeber, 2017, pp. 2011–2012).…”
Section: The Context Of the Studymentioning
confidence: 99%
“…Whereas ethnic minorities often seek better integration into state structures and institutions, Indigenous groups tend to seek greater autonomy from the state (Alfred, 2009;Papillon, 2012). Despite growing recognition that Indigenous political representation should be treated separately from that of ethnic minority representation, many governments continue to conflate the two (Bird, 2014;Kroeber, 2017;Krook & O'Brien, 2010;Lublin & Wright, 2013). As Canessa (2018) has pointed out, there are many cases of peoples recognized as Indigenous in Geneva (ILO headquarters) or New York (UN headquarters) but not in their own countries.…”
mentioning
confidence: 99%